A Role for Maternal Factors in Suppressing Cytoplasmic Incompatibility - Momtaz, AJM Zehadee; Ahumada Sabagh, Abraham D.; Gonzalez Amortegui, Julian G.; Salazar, Samuel A.; Finessi, Andrea; Hernandez, Jethel; Christensen, Steen; Serbus, Laura R. (Frontiers in Microbiology, 2020)
Wolbachia are maternally transmitted bacterial endosymbionts, carried by approximately half of all insect species. Wolbachia prevalence in nature stems from manipulation of host reproduction to favor the success of infected females. The best known reproductive modification induced by Wolbachia is referred to as sperm-egg Cytoplasmic Incompatibility (CI). In CI, the sperm of Wolbachia-infected males cause embryonic lethality, attributed to paternal chromatin segregation defects during early mitotic divisions. Remarkably, the embryos of Wolbachia-infected females “rescue” CI lethality, yielding egg hatch rates equivalent to uninfected female crosses. Several models have been discussed as the basis for Rescue, and functional evidence indicates a major contribution by Wolbachia CI factors. A role for host contributions to Rescue remains largely untested. In this study, we used a chemical feeding approach to test for CI suppression capabilities by Drosophila simulans. We found that uninfected females exhibited significantly higher CI egg hatch rates in response to seven chemical treatments that affect DNA integrity, cell cycle control, and protein turnover. Three of these treatments suppressed CI induced by endogenous wRi Wolbachia, as well as an ectopic wMel Wolbachia infection. The results implicate DNA integrity as a focal aspect of CI suppression for different Wolbachia strains. The framework presented here, applied to diverse CI models, will further enrich our understanding of host reproductive manipulation by insect endosymbionts.